PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Utama, Yayak Ardy Pranata; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out the influence of profitability, leverage and dividend policy to the firm value and the firm size as the moderating variable on the companies which are incorporated in the Jakarta Islamic Index (JII). This research has been done by using purposive sampling as the sample collection technique with certain criteria so 23 companies which are incorporated in the Jakarta Islamic Index have been selected as the research samples. The research data is the secondary data which has been obtained from STIESIA Indonesia Stock Exchange Corner. The hypothesis test has been done by using Moderate Regression Analysis (MRA), with the support of SPSS 20 version. The result of this research is based on the goodness of fit shows that the regression model is feasible to be used to predict the influence of profitability, leverage, dividend policy to the firm value with the firm size as the moderating variable on the companies which are incorporated in the Jakarta Islamic Index. The coefficient determination test (R2) has quite firm contribution. The hypothesis test has been done by using t statistic test which has generated the result that profitability (ROE) variable has positive influence to the firm value (Tobin Q), leverage (DER) has negative influence to the firm value (DER), dividend policy (DPR) does not have any influence to the firm value (TOBIN Q), and firm size (UP) also does not have any ability to moderate the correlation of profitability (ROE), leverage (DER), and Devident policy (DPR) to the firm value (Tobin Q).Keywords: Financial Performance, Firm Size, Firm Value.